2006
DOI: 10.1002/pmic.200600187
|View full text |Cite
|
Sign up to set email alerts
|

The ROP2 family ofToxoplasma gondii rhoptry proteins: Proteomic and genomic characterization and molecular modeling

Abstract: Four rhoptry proteins (ROP) of Toxoplasma gondii previously identified with mAb have been affinity purified and analyzed by MS; the data obtained allowed the genomic sequences to be assigned to these proteins. As previously suggested for some of them by antibody crossreactivity, these proteins were shown to belong to a family, the prototype of which being ROP2. We describe here the proteins ROP2, 4, 5, and 7. These four proteins correspond to the most abundant products of a gene family that comprises several m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
162
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(167 citation statements)
references
References 51 publications
0
162
0
5
Order By: Relevance
“…ROP2 is associated with evacuoles shortly after invasion and ultimately decorates the PVM [40]. Whereas initial experiments indicated that ROP2 is anchored to the PVM by a transmembrane domain [34], this conclusion has been reassessed recently [41,42]. Nonetheless, there is agreement that the N-terminal portion of ROP2 is exposed to the host cytosol.…”
Section: Mitochondria and Ermentioning
confidence: 99%
See 3 more Smart Citations
“…ROP2 is associated with evacuoles shortly after invasion and ultimately decorates the PVM [40]. Whereas initial experiments indicated that ROP2 is anchored to the PVM by a transmembrane domain [34], this conclusion has been reassessed recently [41,42]. Nonetheless, there is agreement that the N-terminal portion of ROP2 is exposed to the host cytosol.…”
Section: Mitochondria and Ermentioning
confidence: 99%
“…The carboxy-terminal portion of ROP4 displays the characteristic kinase domain. However, the lysine (subdomain II) and aspartic acid (subdomain VIb) residues typically necessary for kinase activity are absent [41]. Intriguingly, the mature form of ROP4 is phosphorylated on several serine and threonine residues following the parasite invasion.…”
Section: Proteins Associated With the Pvmmentioning
confidence: 99%
See 2 more Smart Citations
“…Although not apparent for an IRG‐specific function of ROP5 in our own experiments (Fleckenstein et al ., 2012), an interaction of ROP5 with ROP18 was reported to control T. gondii virulence by up‐regulation of ROP18 activity (Behnke et al ., 2012). The rop5 locus is represented by a cluster of tandemly repeated genes encoding three different ROP5 isoforms, ROP5A, ROP5B and ROP5C, each containing multiple copies, and all isoforms are predicted to be catalytically inactive (El Hajj et al ., 2006; Reese and Boothroyd, 2011). Individual sequences of these rop5 paralogues are almost identical within strains but differ considerably between T. gondii types I, II and III strains (Behnke et al ., 2011; Reese et al ., 2011; Niedelman et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%